2006
DOI: 10.1007/s10620-005-9035-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Cytochrome P-450 Activity During Rabeprazole Treatment in Patients with Gastresophageal Reflux Disease

Abstract: Proton pump inhibitors (PPIs) are the cornerstone in the treatment of gastresophageal reflux disease (GORD). PPIs are metabolized by the hepatic cytochrome P-450 enzymes (CYP-450). Rabeprazole is a PPI whose metabolism shows fewer interactions compared to other PPIs. In this study we evaluated the influence of rabeprazole administration on hepatic CYP-450 activity as measured by the (13)C-aminopyrine breath test ((13)C-ABT) in a group of patients with GORD. (13)C-ABT was performed on five GORD patients both be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…These investigators performed [ 13 C]-ABT during rabeprazol in patients with gastroesophageal reflux disease and showed that 1-week, full-dose rabeprazole does not display any significant interactions with CYPs. 25 The present study reconfirmed that rabeprazole has little inhibitory effect on CYP activity as assessed by [ 13 C]-ABT. Our study also demonstrated that omeprazole and lansoprazole inhibit CYP activity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These investigators performed [ 13 C]-ABT during rabeprazol in patients with gastroesophageal reflux disease and showed that 1-week, full-dose rabeprazole does not display any significant interactions with CYPs. 25 The present study reconfirmed that rabeprazole has little inhibitory effect on CYP activity as assessed by [ 13 C]-ABT. Our study also demonstrated that omeprazole and lansoprazole inhibit CYP activity.…”
Section: Discussionsupporting
confidence: 76%
“…Giannini et al 24 also reported in another study that rabeprazole did not inhibit CYP activity in eradication of H pylori with antimicrobial agents. These investigators performed [ 13 C]‐ABT during rabeprazol in patients with gastroesophageal reflux disease and showed that 1‐week, full‐dose rabeprazole does not display any significant interactions with CYPs 25 . The present study reconfirmed that rabeprazole has little inhibitory effect on CYP activity as assessed by [ 13 C]‐ABT.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, the peculiar pharmacokinetics and pharmacodynamics of rabeprazole allow a faster onset of action, and more rapid inhibition of proton pumps than other PPIs, 32, 33 thus making this drug more suitable for short‐term eradication treatment because both fast activation and rapid onset of gastric acid suppression are especially needed in short‐term therapy. Moreover, rabeprazole has relevant in vitro antimicrobial activity, 34, 35 and its administration does not seem to interfere with cytochrome P‐450 activity 36, 37 . This is especially important as in this study, and as happens in everyday clinical practice, approximately half of the patients were on co‐medication, and in this setting the occurrence of drug–drug interactions is more likely.…”
Section: Discussionmentioning
confidence: 58%
“…Benzimidazole-based PPIs are often challenged by having their effects influenced by individual hepatic CYP activity. 15,16 Unlike esomeprazole or lansoprazole, 17 omeprazole is more dependent on the CYP2C19 genotype. 18 The current study also shows less effect by CYP2C19 on ilaprazole than on omeprazole.…”
Section: Discussionmentioning
confidence: 99%